2018
DOI: 10.21873/invivo.11349
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Activity of Betulinic Acid and Betulin in Canine Cancer Cell Lines

Abstract: Both compounds showed an antitumor activity, and the effects of BA were stronger than that of BT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 38 publications
(26 reference statements)
2
28
0
1
Order By: Relevance
“…The cell population increased in S-phase with increasing treatment time, with cells passing from G1-phase to S-phase while DNA synthesis stopped, showing a block at S-phase. This observation is also supported by the earlier literature reports on cytotoxic effect of BA on CL-1 and D17 cells 17 . Furthermore, a slight increase in G2/M ratio occurred due to an increase in treatment time.…”
Section: Resultssupporting
confidence: 91%
“…The cell population increased in S-phase with increasing treatment time, with cells passing from G1-phase to S-phase while DNA synthesis stopped, showing a block at S-phase. This observation is also supported by the earlier literature reports on cytotoxic effect of BA on CL-1 and D17 cells 17 . Furthermore, a slight increase in G2/M ratio occurred due to an increase in treatment time.…”
Section: Resultssupporting
confidence: 91%
“…In this study (+)-betulin exhibited significant cell growth inhibition in human breast cancer cells and in previous studies it did so against canine cancer cells (8). The present study demonstrated that (+)-betulin inhibits the NF-ĸB complex both in vitro (in MDA-MB-231 breast cancer cells), in vivo (in zebrafish) and in silico.…”
Section: Discussionsupporting
confidence: 76%
“…Natural products are recognized as source of lead compounds for the pharmaceutical industry; an example of its active molecule is betulinic acid (BA), a pentacyclic lupane-type triterpenoid found in some plants (Figure 1). This compound is reported to be an antiviral agent and have antidiabetic, antitumoral, antihyperlipidemic, and anti-inflammatory activities [29,30,31,32,33,34]; however, the reports about its antimicrobial activity are controversial [35,36,37,38]. Taking into account the medicinal properties of BA, we evaluated its effects on the SOS response induced by ciprofloxacin, and evaluated whether this action was associated to a reduction of the progress of drug-tolerance in S. aureus .…”
Section: Introductionmentioning
confidence: 99%